Exploring stroke: the role of infection, inflammation and other comorbidities - Learoyd, Annastazia (2017)
Recovery from a stroke is affected by a wide range of factors. A multitude of comorbidities, including old age and diabetes, all increase the risk of death or disability as a result of a stroke. In addition, medical complications can affect stroke outcome. Infections are known to increase the risk of death or disability when contracted in the first week after stroke onset. However, by analysing data from a clinical trial, we have found that infections are actually detrimental for a lot longer than one week. Any infection acquired in the first 76 days after stroke increases the risk of death in comparison to patients with other post-stroke medical complications. Additionally, patients who contract infections and survive up to 90 days post-stroke have more disabilities and are more reliant on assistance compared to stroke patients who did not acquire medical complications.